The Preparation and analysis of financial statements - Padilla, Nicanor B., Jr. ([Manila, Philippines] : [GIC Enterprises & Co., Inc.], 1994)
This book was written to fill a long-felt need for a book devoted solely to financial statements and its analysis and interpretation.
Preparation and analysis of financial statements /, The